Case Report: A Novel ABCC8 Variant in a Chinese Pedigree of Maturity-Onset Diabetes of the Young - Tang, Chaoyan; Meng, Liheng; Zhang, Ping; Liang, Xinghuan; Dang, Chaozhi; Liang, Hui; Wu, Junfeng; Lan, Haiyun; Qin, Yingfen (Frontiers in Endocrinology, 2021)
Background: We aimed to analyze a novel ABCC8 variant of a Chinese patient with suspected maturity-onset diabetes of the young (MODY) and to provide evidence for precise diagnosis and appropriate treatment. Method: A Chinese family with suspected MODY was recruited in this study, which included a 15-year-old female patient with diabetes. Clinical data and blood samples were collected from the proband and other family members. All of the living relatives were given an oral glucose tolerance test. Next-generation sequencing was performed to identify the mutated genes in the proband. Sanger sequencing was utilized to confirm the location of the pathogenic variant in all subjects. Further treatment was referred to targeted family members according to genetic testing. Results: The proband was found to have a random blood glucose level of 244.8 mg/dl and an HbA1c level of 9.2%. Before this investigation, her grandparents had been diagnosed with diabetes. The proband’s second uncle, two aunts, mother, and her cousin were diagnosed with diabetes by abnormal HbA1C (6.5 12.1%) and fasting blood glucose (FBG, 91.4 189.7 mg/dl). The proband’s second aunt had impaired glucose homeostasis (HbA1C=6.4% and FBG=88.0 mg/dl). One novel missense variant c.1432G>A (p.A478T) in exon 9 of the ABCC8 gene was detected in the proband with suspected MODY. The variant was also found in six family members with diabetes or impaired glucose homeostasis including her second uncle, two aunts, mother, and cousin. After treatment was switched to glimepiride, fasting blood glucose was adjusted to 99.54 mg/dl, 2-h postprandial blood glucose was 153.54 mg/dl, serum fructosamine was 259 μmol/l, and HbA1c was 5.8%. Glycemic control remained optimal, and no hypoglycemic episodes were observed in the living relatives. Conclusion: This study revealed one novel missense variant of the ABCC8 gene in Chinese families. The present findings indicated that members of this family responded to treatment with sulfonylureas as previously seen in ABCC8 MODY.